Can addition of frozen section analysis to preoperative endometrial biopsy and MRI improve identification of high-risk endometrial cancer patients? - Go Nakai (BMC, 2021)
Abstract Background Surgeons sometimes have difficulty determining which result to favor when preoperative results (MRI + preoperative endometrial biopsy [pre-op EB]) differ from intraoperative frozen section histology (FS) results. Investigation of how FS can complement ordinary preoperative examinations like MRI and pre-op EB in identification of patients at high risk of lymph node metastasis (high-risk patients) could provide clarity on this issue. Therefore, the aim of this study is to assess the utility of pre-op EB, MRI and FS results and determine how to combine these results in identification of high-risk patients. Methods The subjects were 172 patients with endometrial cancer. Patients with a histological high-grade tumor (HGT), namely, grade 3 endometrioid cancer, clear cell carcinoma or serous cell carcinoma, or with any type of cancer invading at least half of the uterine myometrium were considered high-risk. Tumors invading at least half of the uterine myometrium were classified as high-stage tumors (HST). We compared (a) detection of HGT using pre-op EB versus FS, (b) detection of HST using MRI versus FS, and (c) identification of high-risk patients using MRI + pre-op EB versus FS. Lastly, we determined to what degree addition of FS results improves identification of high-risk patients by routine MRI + pre-op EB. Results (a) Sensitivity, specificity, and accuracy for detecting HGT were 59.6, 98.4 and 87.8% for pre-op EB versus 55.3, 99.2 and 87.2% for FS (P = 0.44). (b) These figures for detecting HST were 74.4, 83.0 and 80.8% for MRI versus 46.5, 99.2 and 86.0% for FS (P < 0.001). (c) These figures for identifying high-risk patients were 78.3, 85.4 and 82.6% for MRI + pre-op EB versus 55.1, 99.0 and 81.2% for FS (P < 0.001). The high specificity of FS improved the sensitivity of MRI + pre-op EB from 78.3 to 81.2%, but this difference was not statistically significant (P < 0.16). Conclusion Frozen section enables identification of high-risk patients with nearly 100% specificity. This advantage can be used to improve sensitivity for identification of high-risk patients by routine MRI + pre-op EB, although this improvement is not statistically significant.